RITUS BARONG WAE SEBAGAI ALTERNATIF RITUS SAKRAMENTALI PEMBERKATAN MATA AIR DALAM LINGKUP GEREJA KATOLIK MANGGARAI - Kiven, Agustinus Fransiskus Naring; Sudir, Yohanes (UNIKA Santo Thomas, 2025)
Barong wae is a rite carried out by the Manggarai people to honor and bless spring as a gift from God. The barong wae rite contains the meaning of maintaining a harmonious relationship between humans and nature. This article aims to analyze the meaning, relevance, and implementation of the barong wae rite as an alternative to sacramental rite of spring blessing. The analysis of this article uses the literature study method. The results of this analysis show that the barong wae rite has a meaning that is in line with the teachings of the Catholic Church regarding the close relationship between humans and God, each other, and their environtment. It is hoped that these results can contribute to the understanding of the barong wae rite as an alternative spring blessing rite.